2015
DOI: 10.1177/0003489415595238
|View full text |Cite
|
Sign up to set email alerts
|

Canalplasty for Exostoses With Maximal Skin Preservation With Temporoparietal Fascia Grafting and Use of Bone Wax for Skin Flap Protection

Abstract: The proposed technique is a safe and effective method of canalplasty for exostoses that imparts accelerated wound healing and minimizes the rate of recurrent stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…Minimizing trauma to the native EAC skin during surgery and preserving its vasculature is critical to allow for postoperative EAC healing. 13 While one patient developed thermal injury due to the ultrasonic serrated knife which resulted in slower ear canal healing, our study indicated that the process of ear canal healing was overall unchanged when compared to a micro-osteotome only technique. This occurred in the first patient in our series.…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…Minimizing trauma to the native EAC skin during surgery and preserving its vasculature is critical to allow for postoperative EAC healing. 13 While one patient developed thermal injury due to the ultrasonic serrated knife which resulted in slower ear canal healing, our study indicated that the process of ear canal healing was overall unchanged when compared to a micro-osteotome only technique. This occurred in the first patient in our series.…”
Section: Discussionmentioning
confidence: 65%
“…The rate of intraoperative complications from the different surgical methods has been shown to be overall low. 6,13,19,20 Our standard transcanal excision of exostoses with micro-osteotome only similarly demonstrates an overall low rate of complications (6.3%) with an even lower rate with the transcanal use of Sonopet (0%), despite this patient population having a higher rate of preoperative stenosis.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations